Theoretical and Methodical aspects of organizational competitive advantages’ management - M. Zhukova (Вестник университета)
The paper deals with the features of competitive advantages as an object of management. The comparative analysis of main approaches to creating competitive advantages is carried out, which allows the authors to conclude that it is necessary to integrate existing approaches. The paper also substantiates the feasibility of using stakeholder analysis and scenario approach in the process of managing competitive advantages. The authors offer a basic scheme for managing competitive advantages, show the interconnection of different approaches and their contribution to creating sustainable competitive advantages.